Love and the turning seasons : India's poetry of spiritual & erotic longing - Schelling, Andrew (Alph Books, 2018)
"For thousands of years, the Indian subcontinent has proved a fertile ground for the world's most captivating erotic love poetry, and the genius of its devotional writing harnesses great energy and mystical insight. It is in fact often hard to tell whether the poets are offering poems of spiritual longing using the garment of love poetry or writing erotic pieces in the guise of devotion. perhaps, in a land where erotic sculpture routinely ornaments its many temples and gods are known for their explosive sexuality, this question has little meaning to these remarkable writers. In their devotional traditions, eroticism and mysticism seem inseparable" --